Triphenylamine derived titanium oxo clusters: an approach to effective organic–inorganic hybrid dyes for photoactive electrodes. Issue 71 (17th August 2018) - Zou, Dan-Hong; Cui, Li-Na; Liu, Pei-Yi; Yang, Shen; Zhu, Qin-Yu; Dai, Jie
Abstract : Titanium oxo clusters (TOCs) anchored with photoactive triphenylamine dyes are reported for the first time. They are unusual TOCs modified with real applied dyes. Using these TPA dye pre-anchored TOCs as organic–inorganic hybrid dyes has advantages for DSSC applications. Abstract : Titanium oxo clusters (TOCs) anchored with photoactive triphenylamine (TPA) dyes are reported for the first time. The TiO2 electrodes modified with the TPA dye pre-anchored TOCs showed excellent photocurrent response properties.